1996
DOI: 10.1007/s004360050142
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the ultrastructure and viability of the cystic stage of Blastocystis hominis from human feces

Abstract: This report describes the ultrastructure and viability of cysts of Blastocystis hominis from feces of infected patients. The cysts were round to ovoid, measured 2-5 microns in size, and contained a condensed cytoplasm that had vacuoles of varying sizes, four nuclei, and as many as six cristate mitochondria. The cell wall was rather electron-lucent. Surprisingly, chromatoid-like structures were found in the cytoplasm and nucleus of some of the cysts. These have not previously been reported in Blastocystis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 13 publications
1
40
0
1
Order By: Relevance
“…One report (237) described the presence of large multinucleate cysts from the stools of Macaca monkeys, which were 15 m in size, and this was suggested to be an indication of differences among Blastocystis species. Blastocystis cysts were reportedly able to survive in water for up to 19 days at a normal temperature but are fragile at extreme temperatures and in common disinfec- tants (154). A later study (306) showed that cysts could survive up to 1 month at 25°C and 2 months at 4°C.…”
Section: Morphological Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…One report (237) described the presence of large multinucleate cysts from the stools of Macaca monkeys, which were 15 m in size, and this was suggested to be an indication of differences among Blastocystis species. Blastocystis cysts were reportedly able to survive in water for up to 19 days at a normal temperature but are fragile at extreme temperatures and in common disinfec- tants (154). A later study (306) showed that cysts could survive up to 1 month at 25°C and 2 months at 4°C.…”
Section: Morphological Formsmentioning
confidence: 99%
“…The cyst form ( Fig. 1A and 3) is the most recently described form of the parasite, and the late discovery is due to its small size (2 to 5 m), which can result in confusion with fecal debris, and the observation that cysts are infrequently seen in laboratory culture (46,153,154,234,312). The cysts are variable in shape but are mostly ovoid or spherical.…”
Section: Morphological Formsmentioning
confidence: 99%
“…This is not surprising since the transmissible form of the parasite is the water-resistant cyst (154). In a study involving a Thai army population, Blastocystis was found to be the most common (21.9%) intestinal parasite (248).…”
Section: Epidemiology and Prevalencementioning
confidence: 99%
“…However, the cyst form appears resistant to some environmental conditions. One experimental study (Moe et al, 1996) found that cysts from the faeces of a symptomatic patient were able to maintain viability, as assessed by subsequent culture techniques, for up to 19 days in water at room temperature, and up to 14 days in water at 48C. Blastocystis has been isolated from sewage, using culture techniques .…”
Section: Prevention and Controlmentioning
confidence: 99%